Bicyclic diironcryptates with mobile guest cations: A new class of solid ionic conductors - Puchta, Ralph; Roling, Bernhard; Scheurer, Andreas; Weiskopf, Verena; Hampel, Frank; van Eikema Hommes, Nico; Hummel, Hans-Ulrich (Solid State Ionics, 2008)
Polycrystalline bicyclic diironcryptates with different mobile guest cations were synthesized and characterized by XRD analysis, IR spectroscopy, FAB-mass spectroscopy, elemental analysis, electrical conductivity spectroscopy and ion exchange experiments. We find strong indication that the guest cations exhibit a long-range mobility and that their mobility is governed by their size relative to the size of the cryptand molecules. On the other hand, the valence of the guest cations seems to play a minor role for the mobility. These results are discussed in comparison to the properties of conventional solid cationic conductors. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: supramolecular chemistry; metallacryptates; cationic conductor; conductivity spectroscopy; ion exchange